2020
DOI: 10.1002/bab.2034
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of nanomaterials as potential immobilization supports for whole cell biocatalysts and cell toxicity effects

Abstract: The traditional approach of fermentation by a free cell system has limitations of low productivity and product separation that need to be addressed for production enhancement and cost effectiveness. One of potential methods to solve the problems is cell immobilization. Microbial cell immobilization allows more efficient up-scaling by reducing the nonproductive growth phase, improving product yield and simplifying product separation. Furthermore, the emergence of nanomaterials such as carbon nanotubes, graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…The cell biological effects of nanomaterials mainly include the transmembrane mechanism, intracellular localization and metabolism, cell viability, cell proliferation, and apoptosis. Studies have shown that nanoparticles enter cells through pinocytosis ( Ehsani et al, 2022 ; Abdul Manaf et al, 2021 ; Liu et al, 2019 ; Reshma et al, 2017 ). This process of binding nanomaterials to carriers and receptors on the cell surface causes denaturation of the relevant protein structures and receptors, resulting in blocked nutrient acquisition and cell growth inhibition ( Lee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cell biological effects of nanomaterials mainly include the transmembrane mechanism, intracellular localization and metabolism, cell viability, cell proliferation, and apoptosis. Studies have shown that nanoparticles enter cells through pinocytosis ( Ehsani et al, 2022 ; Abdul Manaf et al, 2021 ; Liu et al, 2019 ; Reshma et al, 2017 ). This process of binding nanomaterials to carriers and receptors on the cell surface causes denaturation of the relevant protein structures and receptors, resulting in blocked nutrient acquisition and cell growth inhibition ( Lee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cell immobilization involves physical or chemical fixation of cells onto or into a support, for example, adsorption of cells on a surface, cell flocculation, covalent binding of cells to a carrier, cell entrapment, and cell encapsulation (Abdul Manaf et al, 2020;Boura et al, 2022). Cell immobilization can improve cell stability, allowing for easier cell separation and reuse, and can protect the cells from environmental stresses such as changes in temperature, pH, or solvent (Eş et al, 2015;Guzik et al, 2014;Lapponi et al, 2022).…”
Section: Research Articlementioning
confidence: 99%
“…According to Abdul Manaf et al [3], cell immobilization is a method of attaching cells onto or inside a support via a variety of techniques, such as mechanical containment behind a barrier, adsorption on a solid support, and flocculation. Cell immobilization could protect the cells from shear forces inside the bioreactor during the synthesis of desired enzymes and products.…”
Section: Introductionmentioning
confidence: 99%